Is dehulling of peas and faba beans necessary prior to dry fractionation for the production of protein- and starch-rich fractions? Impact on physical properties, chemical composition and techno-functional properties. (August 2020) - Saldanha do Carmo, Cátia; Silventoinen, Pia; Nordgård, Catherine Taylor; Poudroux, Claire; Dessev, Tzvetelin; Zobel, Hanne; Holtekjølen, Ann Katrin; Draget, Kurt Ingar; Holopainen-Mantila, Ulla; Knutsen, Svein Halvor; Sahlstrøm, Stefan
Abstract: Dehulling of peas and faba beans prior to milling and air classification was evaluated, namely its impact on physical properties, chemical composition and techno-functional properties of the fractions. Dry fractionation protocols for protein enrichment from whole and dehulled peas and faba beans were optimized and large-scale batches were produced. Fine fractions with protein contents of 44.0 and 46.2% dm from whole and dehulled peas and between 60.0 and 60.9% dm from whole and dehulled faba beans were obtained, respectively. A maximum protein recovery of 71.3% and 49.2% was obtained for peas and faba beans, respectively. Dehulling enabled a lighter colour of faba bean fractions and improved the starch enrichment in the coarse fractions from peas and faba beans. The total non-starch polysaccharides were significantly reduced in the coarse fractions when dehulling was conducted. Dehulling did not significantly improve the techno-functional properties of fine and coarse fractions. Graphical abstract: Image 1 Highlights: Protein-rich fractions were obtained by dry fractionation of peas and faba beans. Dehulling had no significant impact on protein-enrichment in the fine fractions. Dehulling increased the starch-enrichment in the coarse fractions. Dehulling reduced the total non-starch polysaccharides in the coarse fractions. Dehulling didn't significantly affect the techno-functional properties of fractions.